Procesiranje vakuumskih izolacijskih panelov - Nemanič, Vincenc (Kovine zlitine tehnologije, 1997)
All metal vessels with which thermal insulating vacuum has to be preserved forsome years, must be prepared very carefully regarding cleaning and processing. Limits for leaking and outgassing are practically the same as for UHV chambers. Evacuatead panel, consisted from two metal foils supported by discrete supports can exhibit excellent thermal insulating properties. It's unusual shape, thin walls and local mechanical strain restrict conditions at vacuum processing. Preparation of test samples, pumped through tube with small conductance, is addditionaly troublesome. In the paper, basic vacuum demands, theoretical and practical limitations of material selection, cleaning, welding and pumping are given. Measured pressure rise slope of test samples is compared to literature data for thick wall chambers.
Keywords: vakuumska tehnika; vakuumska toplotna izolacija; tesnjenje; toplotna izolacija; razplinjevanje